2016
DOI: 10.1021/acs.energyfuels.5b02143
|View full text |Cite
|
Sign up to set email alerts
|

Mesophilic and Thermophilic Biohydrogen Production from Xylose at Various Initial pH and Substrate Concentrations with Microflora Community Analysis

Abstract: Anaerobic dark fermentation biohydrogen production from xylose was investigated under mesophilic (35 °C) and thermophilic (55 °C) conditions at various initial pH (5.0–10.0) and substrate concentrations (2.5–12.5 g/L). In addition, the microbial community structure variations under different temperatures were analyzed. It was demonstrated that the maximum hydrogen yield (1.24 mol-H2/mol-xylose) was obtained with substrate concentration of 7.5 g/L and initial cultivation, pH 7.0, at 35 °C, with butyrate, acetat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…Peak hydrogen yield obtained at 55°C revealed that thermophilic hydrogen‐producing bacteria have been enriched by repeated batch cultivation. High hydrogen production efficiency gained at 55°C could be attributed to higher bioactivity in the thermophilic range . Higher hydrogen production with few by‐products has also been observed under thermophilic conditions in comparison with mesophilic conditions in a previous study .…”
Section: Discussionmentioning
confidence: 56%
See 4 more Smart Citations
“…Peak hydrogen yield obtained at 55°C revealed that thermophilic hydrogen‐producing bacteria have been enriched by repeated batch cultivation. High hydrogen production efficiency gained at 55°C could be attributed to higher bioactivity in the thermophilic range . Higher hydrogen production with few by‐products has also been observed under thermophilic conditions in comparison with mesophilic conditions in a previous study .…”
Section: Discussionmentioning
confidence: 56%
“…High hydrogen production efficiency gained at 55°C could be attributed to higher bioactivity in the thermophilic range . Higher hydrogen production with few by‐products has also been observed under thermophilic conditions in comparison with mesophilic conditions in a previous study . Although, with lower hydrogen yield at 60°C (1.04 mol H 2 mol −1 xylose consumed ), heat pretreatment was not needed to inhibit methane‐producing bacteria during repeated batch culture at 60°C and at 65°C.…”
Section: Discussionmentioning
confidence: 68%
See 3 more Smart Citations